Differentiated origins: trajectories of transcultural knowledge in Laos and beyond - Sprenger, Guido (Sojourn, 2011)
Ethnicity belongs to the most important types of differentiation in Laos. Among the means to establish such differences is the ascription of bodies of knowledge to various ethnicities. Ritual healing knowledge is often associated with the foreign and the culturally different. The attribution of differentiated categories of foreignness thus supports the emergence and reproduction of ethnic differentiation and interethnic communication in this region. This article compares ritual healing among Rmeet in Laos, Karen in Thailand, and Iu Mien in both countries in respect to the ethnotopography of its origins. (Sojourn/GIGA)
Keywords: Laos; Thailand